Catecholamine-Induced Cardiomyopathy in Pheochromocytoma: How to Manage a Rare Complication in a Rare Disease? - Santos, Jenn Rachelle U.; Brofferio, Alessandra; Viana, Bruna; Pacak, Karel (Hormone and Metabolic Research, 2018)
Pheochromocytomas and paragangliomas (PHEOs) are rare neuroendocrine tumors. Clinical manifestations include different cardiovascular signs and symptoms, which are related to excessive secretion of catecholamines. Catecholamine-induced cardiomyopathy in PHEO (CICMPP) is a rare but dreaded complication of PHEO. Once patient is diagnosed with this condition, the prognosis is worse and a surgical risk is much higher than expected. This article focuses on how catecholamines affect the heart and the pathophysiologic mechanism of CICMPP. The cardiovascular responses to catecholamine depend mostly on which catecholamine is released as well as the amount of catecholamine that is released. The acute release of norepinephrine and epinephrine from PHEO increases heart rate, systemic vascular resistance, myocardial contractility, and reduces venous compliance. The excessive adrenergic stimulation by catecholamine results in severe vasoconstriction and coronary vasospasm, myocardial ischemia, and subsequently damage, and necrosis. Chronically elevated catecholamine levels lead to significant desensitization of cardiac β-adrenoceptors. The increased levels of the enzyme β-adrenoceptors kinase (βARK) in the heart seems to mediate these biochemical and physiological changes that are consistently correlated with attenuated responsiveness to catecholamine stimulation. Through these mechanisms different types of cardiomyopathy (CMP) can be formed. This review discusses extensively the 3 types of cardiomyopathies that can be present in a PHEO patient. It also provides the clinical presentation and diagnostic and therapeutic algorithm in managing patients with CICMPP.
Keywords: cardiomyopathy; pheochromocytoma; paraganglioma; catecholamine